1997
DOI: 10.1096/fasebj.11.7.9212075
|View full text |Cite
|
Sign up to set email alerts
|

Biochemistry and molecular biology of plant sulfotransferases

Abstract: It is now well established that, in mammals, sulfate conjugation constitutes an important reaction in the transformation of xenobiotics and in the modulation of the biological activity of steroid hormones and neurotransmitter. The presence of a sulfate group on some molecules can also be a prerequisite for their biological function. For example, it is well known that the sulfate groups are directly involved in the molecular interaction between heparin and antithrombin III. In plants, sulfation also seems to pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
68
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(69 citation statements)
references
References 33 publications
1
68
0
Order By: Relevance
“…The K m values for PAPS, determined with fixed concentration of kaempferol-3-glucoside, was 0.4 mM. which is within the range of K m values (0.2 0.4 mM) previously reported for other flavonoid sulfotransferases (21).…”
Section: Flavonoid Glycoside Sulfation By Atsult202b7supporting
confidence: 84%
See 1 more Smart Citation
“…The K m values for PAPS, determined with fixed concentration of kaempferol-3-glucoside, was 0.4 mM. which is within the range of K m values (0.2 0.4 mM) previously reported for other flavonoid sulfotransferases (21).…”
Section: Flavonoid Glycoside Sulfation By Atsult202b7supporting
confidence: 84%
“…4). Previous studies have shown that flavonol sulfotransferases derived from Flaveria species displayed optimum pH ranging 6.0 8.5 (21). Considering that the vacuolar pH of plant cells is about 5.0 5.5 (22) and that the flavonol glycosides accumulates mainly in the vacuole (23), it is possible that AtSULT202B7 might somehow be transported into this acidic organelle and sulfate the flavonol glycosides locally as substrates.…”
Section: Flavonoid Glycoside Sulfation By Atsult202b7mentioning
confidence: 99%
“…Plastids contain all the enzymes necessary for reductive assimilation of sulfate (Schiff, 1983;Schmidt, 1986). However, all known sulfotransferases that carry out sulfate esterification are cytosolic enzymes (Varin et al, 1997), indicating the need for activated sulfate in the cytosol. A cytosolic isoenzyme of ATP sulfurylase has been reported in some plant species (Lunn et al, 1990;Renosto et al, 1993).…”
Section: Cys Is Formed When Sulfide Reacts With O-acetyl Ser (Oas) Mementioning
confidence: 99%
“…Sulfur is assimilated in either the oxidized or the reduced form (Leustek and Saito, 1999). When incorporated in the oxidized form it is used for esterification of a variety of compounds including polysaccharides such as carrageenans and agaroids (McCandless and Craigie, 1979), sulfated flavonoids (Varin et al, 1997), glucosinolates, and many others . Alternatively, sulfate is reduced to sulfide and is then incorporated as the thiol group of Cys.…”
mentioning
confidence: 99%
See 1 more Smart Citation